1974
DOI: 10.3758/bf03198571
|View full text |Cite
|
Sign up to set email alerts
|

Time perception and the filled-duration illusion

Abstract: A reproduction design is used to show that temporal intervals containing brief tones appear longer than empty intervals of the same duration, the effect being independent of duration. These and previous data are discussed within a theoretical framework which allows for the interrelation of data from different time perception tasks; and a reversible encoding model is stated which accounts for much of the data obtained with empty intervals. A "chunking" model, in which tones occurring in an interval serve to seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
152
3
5

Year Published

1983
1983
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(173 citation statements)
references
References 11 publications
8
152
3
5
Order By: Relevance
“…As predicted, interval estimates in the graphemic condition were an increasing function of list length. It is noteworthy that the increasing function obtained in the present graphemic condition is similar to the results of previous prospective studies (Buffardi, 1971;Craig, 1973;Mo, 1975;Thomas & Brown, 1974), which used nonverbal stimuli and required no active processing during the interval.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As predicted, interval estimates in the graphemic condition were an increasing function of list length. It is noteworthy that the increasing function obtained in the present graphemic condition is similar to the results of previous prospective studies (Buffardi, 1971;Craig, 1973;Mo, 1975;Thomas & Brown, 1974), which used nonverbal stimuli and required no active processing during the interval.…”
Section: Discussionsupporting
confidence: 79%
“…In one set of studies (Bakan, 1955; Burnside, 1971;Curton & Lordahl, 1974;DeWolfe & Duncan, 1959;Hicks & Brundige, 1974;McKay, 1977; Vroon, 1970), estimates decreased as the amount of information presented during the interval increased. The second set of studies (Aitken & Gedye, 1968; Buffardi, 1971;Craig, 1973; Mo, 1975; Thomas & Brown, 1974) produced the filled-duration illusion-intervals filled with nonverbal stimuli such as lights or tones were A summary of this paper was presented at the American Psychological Association convention, Washington, D,C., August 1982. I thank Linda Lawrence for assistance in running subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The illusion has been shown for the auditory modality (clicks and continuous tones), visual modality (Xashes and continuous light), and tactile modality (vibrations applied to the index Wnger; short bursts or continuous vibrations). Thomas and Brown (1974) used diVerent frequencies for end point tones and Wller tones, and BuVardi (1971) showed that overestimations increase with the number of Wller elements in all three modalities. Thus, if the haptic Wlled-space illusion for dynamic touch is essentially a variant of the Wlled-duration illusion, the inXuence of Wller density in the former case must have a temporal character.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported a Wlled-duration illusion, i.e., Wlled time intervals judged longer than empty ones (BuVardi 1971;Craig 1973;Goldstone and Goldfarb 1963;Grimm 1934;Otto Roelofs and Zeeman 1951;Thomas and Brown 1974). The illusion has been shown for the auditory modality (clicks and continuous tones), visual modality (Xashes and continuous light), and tactile modality (vibrations applied to the index Wnger; short bursts or continuous vibrations).…”
Section: Discussionmentioning
confidence: 99%